Optimal Selection of Soils and Aggregates Mixtures for a Frost Blanket Course of Road Pavement Structure - Vaitkus, Audrius; Vorobjovas, Viktoras; Žiliūtė, Laura; Kleizienė, Rita; Ratkevičius, Tomas (The Baltic Journal of Road and Bridge Engineering, 2012)
Resistance to frost of road pavement structure is ensured by a functional frost blanket course from frost nonsusceptible soils or aggregate mixtures. The material used and the thickness of frost blanket course must not only ensure the required resistance to frost of road pavement structure but also to increase bearing capacity of the structure, to distribute and reduce pressure to the subgrade surface. The article gives a summary of research on aggregates mixtures and soils used for a frost blanket course and taken from the currently operating quarries in Lithuania. The conclusion of research analysis gives the suggestions for the use of materials for a frost blanket course. Based on the data obtained it is recommended when laying a frost blanket course to take into consideration bulk density and Proctor density of the material used as well as transportation costs.